Strengthening Tax Compliance: Enhancing E-Invoice Effectiveness in Public Sector Environmental Services - Muhammad Taufiq; R Luki Karunia (Trescode Green Organization, 2023)
The Environmental Quality Control Laboratory (LPKL) of Perumda Tirtawening is a Taxable Person for VAT purposes (PKP) responsible for issuing tax invoices for environmental testing services. However, the e-invoice generation process in this business unit faces operational constraints that hinder financial efficiency. This article aims to analyze the effectiveness of consumer e-tax invoice generation, identify obstacles, and provide improvement solutions through a 30 -day practical approach. The methods used were participant observation and in-depth interviews within the Finance Department. The results show a buildup of invoice requests and numerous revisions due to the absence of clear Standard Operating Procedures (SOP). As a solution, a draft SOP for the flow of generating and uploading e-invoices was developed to minimize data entry errors and accelerate the approval process from the head office. The implementation of these recommendations is expected to optimize tax administration compliance and increase consumer satisfaction.